The great successor : the divinely perfect destiny of brilliant Comrade Kim Jong Un - Fifield, Anna (PublicAffairs, 2019)
"Skeptical yet insightful, Fifield creates a captivating portrait of the oddest and most secretive political regime in the world--one that is isolated yet internationally relevant, bankrupt yet in possession of nuclear weapons--and its ruler, the self-proclaimed Beloved and Respected Leader, Kim Jong Un."--Book jacket.